Thyroxine prevents reoxygenation injury in isolated proximal tubule cells - YALÇIN, AHMET SUHA; HAKLAR, GONCAGÜL (SPRINGER, 2003)
Ischemia is characterized by cessation of blood flow and oxygen delivery to tissues that results in disruption of cellular structure and organelles. However, restoration of blood flow following ischemia causes reperfusion injury, characterized by further damage in the tissues mediated by reactive oxygen species. In the kidney, reactive oxygen molecules have been implicated in ischemic, toxic and immunological glomerular damage. Thyroxine has been shown to be cytoprotective in toxic and ischemic injury. Thyroxine's cytoprotective effect is postulated to be secondary to stimulation of intracellular ATP synthesis. However, the underlying mechanism of that beneficial effect remains to be investigated. In this study we investigated the effect of thyroxine (T4) on free oxygen radical production in an in vitro model of reperfusion injury. Free oxygen radical (FOR) levels were determined by a chemiluminescence method after freshly isolated rabbit proximal tubule cells were subjected to 15 min of anoxia followed by 45 min of reoxygenation. Reoxygenation injury resulted in a significant increase in FOR levels (P<0.0001). FOR levels were significantly lower in the group treated with thyroxine (P=0.01) and cells treated with thyroxine displayed better preservation of cellular structure. We conclude that thyroxine's cytoprotective effect might be via decreased synthesis of FOR, and thyroxine treatment may confer cytoprotection in renal conditions characterized by FOR-mediated injury.
Keywords: anoxia-reoxygenation; cellular injury; free oxygen radicals; thyroxine; ACUTE-RENAL-FAILURE; ISCHEMIA-REPERFUSION INJURY; OXYGEN FREE-RADICALS; EPITHELIAL-CELLS; XANTHINE-OXIDASE; SUPEROXIDE-DISMUTASE; RAT; DAMAGE; RABBIT; KIDNEYS